You were always mine : a novel - Baart, Nicole (New York, NY : Atria Books, 2018)
Jessica Chamberlain, a single mother living in a small Iowa town, faces a web of lies when a tragic death in another state leads her to clues that suggest her estranged husband has been in contact with the biological mother of her adopted son, Gabriel.
Keywords: Family life -- Fiction; Domestic fiction; Suspense fiction; Suspense fiction